A spatiotemporal analysis of inequalities in life expectancy and 20 causes of mortality in sub-neighbourhoods of Metro Vancouver, British Columbia, Canada, 1990–2016. (November 2021) - Yu, Jessica; Dwyer-Lindgren, Laura; Bennett, James; Ezzati, Majid; Gustafson, Paul; Tran, Martino; Brauer, Michael
Abstract: Spatially varying baseline data can help identify and prioritise actions directed to determinants of intra-urban health inequalities. Twenty-seven years (1990–2016) of cause-specific mortality data in British Columbia, Canada were linked to three demographic data sources. Bayesian small area estimation models were used to estimate life expectancy (LE) at birth and 20 cause-specific mortality rates by sex and year. The gaps in LE for males and females ranged from 6.9 years to 9.5 years with widening inequality in more recent years. Inequality ratios increased for almost all causes, especially for HIV/AIDS and sexually transmitted infections, maternal and neonatal disorders, and neoplasms. Highlights: A high degree of intra-urban inequality in mortality is present in a city with a high level of average life expectancy. Life expectancy inequality has increased in more recent years for both males and females. Absolute inequality has decreased since 1991 from certain prominent causes, such as neoplasms, cardiovascular diseases, and respiratory infections and tuberculosis. Relative inequality has increased for all causes except for neoplasms. Accounting for population migration within the study area did not substantially impact period life expectancy estimates.